Optimization of the PID-PD parameters of the overhead crane control system by using PSO algorithm - Nur Iffah, Mohamed Azmi; Nafrizuan, Mat Yahya; Ho, Jun Fu; Wan Azhar, Wan Yusoff (EDP Sciences, 2019)
The development of combination of proportional-integral-derivative and proportional-derivative (PID-PD) controller for overhead crane is presented. Due to the pendulum-like settings, the swinging of load has caused many difficulties while operating the overhead crane. Swinging of the load causes unnecessary tension to the cable and structure of the overhead crane, which will compromise the safety of operator and other workers. Overhead cranes should have the ability to move the load to desired point as fast as possible while minimizing the load swing and maintaining the accuracy. Proportional-integral-derivative (PID) controller is used for overhead crane positioning and proportional-derivative (PD) controller for load oscillation. New time-domain performance criterion function is used in particle swarm optimization (PSO) algorithm for the tuning of the PID-PD controller rather than the general performance criteria using error of the system. This performance criterion function monitors the performance in terms of rise time, overshoot, settling time and steady state error of the overhead crane system. The performance of the optimised PID-PD controller is verified with simulation in MATLAB. The PSO optimized PID-PD controllers with new performance criterion are shown effective in improving the step response of the overhead crane position as well as controlled the load oscillation.